2019
DOI: 10.1159/000490044
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Correlates of Hippocampal Atrophy and Ventricular Enlargement in Adults with or without Mild Cognitive Impairment

Abstract: We analyzed structural magnetic resonance imaging data from 58 cognitively normal and 101 mild cognitive impairment subjects. We used a general linear regression model to study the association between cognitive performance with hippocampal atrophy and ventricular enlargement using the radial distance method.Bilateral hippocampal atrophy was associated with baseline and longitudinal memory performance. Left hippocampal atrophy predicted longitudinal decline in visuospatial function. The multidomain ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…For example, the hippocampus is susceptible to the earliest AD neuropathological changes (Frankó et al, 2013), subtle alterations in cerebral hemodynamics over the course of aging (Okonkwo et al, 2014), blood-brain barrier breakdown (Montagne et al, 2015), and hippocampal sclerosis (Barker et al, 2002). Thus, it is not surprising that hippocampal volume is a strong predictor of concurrent (Besson et al, 2015;Seab et al, 1988) and future cognitive (Goukasian et al, 2019;Jack et al, 2000) impairment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the hippocampus is susceptible to the earliest AD neuropathological changes (Frankó et al, 2013), subtle alterations in cerebral hemodynamics over the course of aging (Okonkwo et al, 2014), blood-brain barrier breakdown (Montagne et al, 2015), and hippocampal sclerosis (Barker et al, 2002). Thus, it is not surprising that hippocampal volume is a strong predictor of concurrent (Besson et al, 2015;Seab et al, 1988) and future cognitive (Goukasian et al, 2019;Jack et al, 2000) impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that with CCH, the hippocampus displays acute neuronal damage and cell death originating from the CA4 area, to CA2 and CA3, with the CA1 area being the last zone affected [ 71 , 161 , 162 ]. Decline in memory performance, spatial navigation and visuospatial functions have been observed in patients with hippocampal atrophy [ 163 , 164 ]. While the direct mechanistic explanation for these associations in VCI has not been established, it is suggested that reduced neuronal capacity in the hippocampal area lowers its connectivity with other brain regions [ 163 165 ].…”
Section: Chronic Cerebral Hypoperfusion (Cch): a Primary Driver Of Vcimentioning
confidence: 99%
“…Notably, a recent meta-analysis has demonstrated that habitual PA prevents hippocampal volumetric decreases, which occur over time in humans [ 5 ]. The hippocampus is the primary centre of learning and memory, and since age-related hippocampal atrophy is a strong predictor of future cognitive decline [ 6 , 7 , 8 ], these findings hold promising implications for combating cognitive decline through exercise-induced retention of hippocampal volume.…”
Section: Introductionmentioning
confidence: 99%